Treatment of HBsAg-positive chronic active hepatitis with human fibroblast interferon. Issue 2 (February 1978) - Kingham, J G; Ganguly, N K; Shaari, Z D; Mendelson, R; McGuire, M J; Holgate, S J; Cartwright, T; Scott, G M; Richards, B M; Wright, R
Abstract : Two patients with HBsAg positive chronic active hepatitis have been treated with human fibroblast interferon 10(7) units daily for two weeks. Before treatment, both patients had high levels of hepatitis B surface antigen, core antibody, and DNA-binding antibody in the blood and one patient had a fourfold rise in serum AST. During treatment there was a striking fall in the core antibody titre and also in the DNA-binding antibody, which has been maintained for several months subsequently; in one patient the initially high AST level fell to normal. No significant adverse effects occurred, and these observations should encourage further trials of fibroblasts interferon in hepatitis B.